The efficiency and transversality of traditional boxing skills to several full-contact combat sports: a narrative review - Pinto, F. C. L.; Marinho, D.; Teixeira, J. E.; Forte, P.; Neiva, H. P.; Branquonho, L.; Ferraz, R. (Archives of Budo Science of Martial Arts and Extreme Sports, 2022)
Background and Study Aim: Despite the well-known efficiency of the boxing art, research focused on the effectiveness of boxing skills used in other full-contact combat sports remains limited. Therefore, this study aimed is knowledge about the effectiveness of boxing skills in other full-contact combat sports.